Evaluation of Performance Characteristics on VCR-DI-Diesel Engine Fueled with Coconut Methyl Ester and DI-Ethyl Ether as an Additive - S.Bhanu Teja (International Journal of Advanced Science and Technology, 2020)
The ever-increasing growth of the economies of the developing countries is increasing the demand for conventional fuels like Petrol and Diesel. However, the usage of conventional fuels has detrimental effects like increased pollution and global warming. So, scientists around the world has started looking for environment friendly fuels which are safe to use. Biodiesels are prepared form vegetable oils like linseed, cottonseed and coconut etc. Since these oils cannot be used directly because of their viscosity, we use a process called transesterification to break them down into simpler molecules. In our current experimentation, we have analyzed various performance characteristics of a VCR-DI-Diesel engine using Coconut Methyl Ester as fuel blended with varying concentration of Di-Ethyl Ether (DEE) as an additive. As part of our analysis, we have observed that the performance characteristics of the engine are optimum at 5% concentration of DEE.